Use of different reference values for handgrip strength in individuals with COPD: analysis of agreement, discriminative capacity, and main clinical implications - Jéssica Fonseca; Felipe Vilaça Cavallari Machado; Laís Carolini Santin; Letícia Medeiros; Ana Carolina Andrello; Nidia Aparecida Hernandes; Fabio Pitta (Jornal Brasileiro de Pneumologia, 2022)
ABSTRACT Objective: To identify reference values for handgrip strength through a literature search and compare the agreement of reference values from Brazil with others for handgrip strength in a sample of COPD patients in Brazil, as well as to determine which set of reference values is more discriminative regarding differences in clinical characteristics between individuals with low handgrip strength and normal handgrip strength. Methods: To identify reference values for handgrip strength, a literature search was performed; a retrospective cross-sectional analysis of baseline-only data from two unrelated studies was then performed. Individuals were evaluated for handgrip strength, peripheral muscle strength, respiratory muscle strength, pulmonary function, body composition, exercise capacity, dyspnea, and functional status. Results: Of the 45 studies that were initially selected, 9 met the criteria for inclusion in the analysis, which included 99 COPD patients in Brazil (52% of whom were male with GOLD stage II-IV COPD). The prevalence of low handgrip strength varied across studies (from 9% to 55%), the set of reference values for handgrip strength in a sample of individuals in Brazil having classified 9% of the study sample as having low handgrip strength. The level of agreement between the reference values for a sample of individuals in Brazil and the other sets of reference values varied from weak to excellent. The reference values for a sample of individuals in Brazil showed the highest number of significantly different characteristics between individuals with low and normal handgrip strength. Conclusions: The level of agreement between national and international sets of reference values for handgrip strength varied from weak to excellent in COPD patients in Brazil. Reference values for handgrip strength with higher discriminative capacity are not necessarily those that identify more individuals as having low handgrip strength.